Screening of some Indian medicinal plants for their antimicrobial properties - Ahmad, I.; Mehmood, Z.; Mohammad, F.
A total of 82 Indian medicinal plants traditionally used in medicines were subjected to preliminary antibacterial screening against several pathogenic and opportunistic microorganisms. Aqueous, hexane and alcoholic extracts of each plant were tested for their antibacterial activity using agar well diffusion method at sample concentration of 200 mg:ml. The results indicated that out of 82 plants, 56 exhibited antibacterial activity against one or more test pathogens. Interestingly, extracts of five plants showed strong and broad spectrum activity as compared to rest of 51 plant extracts which demonstrated moderate activity. On the whole the alcoholic extracts showed greater activity than their corresponding aqueous and hexane extracts. Among various extracts, only alcoholic extracts of Emblica officinalis, Terminalia chebula, Terminalia belerica, Plumbago zeylanica and Holarrhena antidysenterica were found to show potentially interesting activity against test bacteria. These active crude alcoholic extracts were also assayed for cellular toxicity to fresh sheep erythrocytes and found to have no cellular toxicity.
Keywords: MEDICINAL PLANTS; ANTIBACTERIAL ACTIVITY; CELLULAR TOXICITY